Neuroprotective Potential of Non-Digestible Oligosaccharides: An Overview of Experimental Evidence - Divyashri, Gangaraju; Sadanandan, Bindu; Chidambara Murthy, Kotamballi N; Shetty, Kalidas; Mamta, Kumari (Frontiers in Pharmacology, 2021)
Non-Digestible Oligosaccharides (NDOs) from dietary sources have potential as prebiotics for neuroprotection. Globally diverse populations suffering from one or the other forms of neurodegenerative disorders is on the rise and NDOs have potential as supportive complimentary therapeutic options against these oxidative linked disorders. Elevated levels of free radicals cause oxidative damage to biological molecules like proteins, lipids and nucleic acids associated with various neurological disorders. Therefore, investigating the therapeutic or prophylactic potential of prebiotic bioactive molecules such as NDOs as supplements for brain and cognitive health has merit. Few prebiotic NDOs have shown promise as persuasive therapeutic solutions to counter oxidative stress by neutralizing free radicals directly or indirectly. Further they are also known to modulate through brain-derived neurotrophic factor (BDNF) through direct and indirect mechanisms conferring neuroprotective and neuromodulating benefits. Specifically, NDOs such as fructo-oligosaccharides (FOS), xylo-oligosaccharides (XOS), isomalto-oligosaccharides (IMO), manno-oligosaccharides (MO) pectic-oligosaccharides (POS) and similar oligosaccharides positively influence overall health via various mechanisms. Increasing evidence has suggested that the beneficial role of such prebiotic NDOs is not only directed towards the colon, but also distal organs including the brain. Despite the wide applications of these classes of NDOs as health supplements, there is limited understanding of the possible role of these NDOs as neuroprotective therapeutics . This review provides important insights into prebiotic NDOs, their source and production with special emphasis on existing direct and indirect evidence of their therapeutic potential in neuroprotection.